A Perspective of Alternative Delivery Mechanisms and Motivated Civil Service for Nepal - Sharma, Durga Nidhi (Administration and Management Review, 2009)
Divided into three parts this article looks at a motivated civil service for Nepal in general and a perspective of alternative service delivery mechanisms in particular. The first part of the article presents civil service in a nutshell. The second part highlights the alternative service delivery mechanisms. In the third part, the focus is on the mechanisms that Nepal should adopt for efficient and effective delivery of public services. Administration and Management Review Vol. 20, No. 1, January, 2008, Page 17-32